Lanthanum enhances biomass and bioactive metabolite production in Glycyrrhiza uralensis via coordinated gene regulation - Shao, Yuanyang; Wang, Yushi; Zhu, Yunhao; Wang, Lei; Wang, Yashun; Guo, Xingyu; Zhai, Enai; Zou, Huiqin; Yan, Yonghong (Frontiers in Plant Science, 2025)
IntroductionGlycyrrhizic acid, liquiritin, and liquiritigenin are key secondary metabolites in Glycyrrhiza uralensis Fisch. with significant pharmacological value. However, their relatively low content in the plant poses a challenge for efficient production. This study aimed to investigate the promotive effect and underlying mechanism of the rare earth element lanthanum (La) on the accumulation of these bioactive compounds.MethodsThe impact of La treatment on Glycyrrhiza uralensis seedlings was systematically evaluated. Biomass parameters, including plant height, root fresh weight, and root dry weight, were measured. The contents of glycyrrhizic acid, liquiritin, liquiritigenin, and related metabolites were quantified using UPLC-MS/MS. The expression levels of key biosynthetic genes were analyzed via transcriptomic sequencing (RNA-seq). The distribution of La in plant tissues was determined by ICP-MS.ResultsLa treatment significantly promoted plant growth, increasing biomass parameters such as plant height, fresh weight, and dry weight. It also enhanced the accumulation of the target secondary metabolites, notably increasing the content of glycyrrhizic acid, liquiritin, and liquiritigenin. Transcriptome analysis revealed that La markedly upregulated the expression of key genes in the biosynthetic pathways: SQE and CYP88D6 in the glycyrrhizic acid pathway, and PAL, C4H, CHS, and 4CL in the liquiritin/liquiritigenin pathway. Significant positive correlations were observed among the La-induced increases in biomass, metabolite content, and the expression levels of these key genes. ICP-MS analysis confirmed substantial root-specific accumulation of La.DiscussionThe results demonstrate that La enhances the accumulation of glycyrrhizic acid, liquiritin, and liquiritigenin via a dual mechanism that simultaneously increases biomass (thereby expanding the precursor pool) and upregulates the expression of key rate-limiting enzyme genes in their biosynthetic pathways. This synergistic action ultimately leads to elevated metabolite production. Our study thereby elucidates the mechanism by which La enhances bioactive metabolite yields in Glycyrrhiza uralensis, proposing a novel strategy for applying rare earth elements to improve the production of valuable compounds in medicinal plants.